ZrCuFeAlAg thin film metallic glass for potential dental applications. (July 2017) - Cai, Chu-Ning; Zhang, Cheng; Sun, Ying-Sui; Huang, Her-Hsiung; Yang, Cong; Liu, Lin
Abstract: In this study, the application of a Ni-free Zr60.14 Cu22.31 Fe4.85 Al9.7 Ag3 thin film metallic glass (TFMG) was examined as an approach to retard the poor tribological properties of Ti-alloys for dental applications. The TFMGs were coated on biomedical Ti6Al4V substrate by single-target magnetron sputtering. The fretting resistance was assessed using a reciprocating tribo-tester against Si3 N4 counterpart in air and in artificial saliva. Bio-corrosion resistance of TFMG-coated Ti6Al4V samples was tested via electrochemical polarizations and electrochemical impedance spectroscopy in artificial saliva. Biocompatibility of the TFMG was tested in vitro, in comparison with that of the Ti6Al4V alloy. The results showed that this TFMG not only possessed 1.8–2.8 times higher fretting resistance than the Ti6Al4V alloy under various tribological conditions, but also lower bio-corrosion rate and superior passive film. In-vitro assessments of cytotoxicity and cell adhesion indicated that the TFMG has no any cytotoxicity and well-flattened cell adhesion morphology, as good as the Ti6Al4V alloy. The present Ni-free Zr-based TFMG is expected to improve the lifetime and quality of biomedical implants or devices for dental applications. Graphical abstract: Highlights: A Ni-free ZrCuFeAlAg TFMG was prepared by using single-target magnetron sputtering. The TFMG shows improved fretting resistance than Ti6Al4V alloy in artificial saliva. The TFMG has lower bio-corrosion rate and superior passive film than Ti6Al4V. Zr-based TFMG exhibits no cytotoxicity and good biocompatibility. This non-toxic TFMG is promising candidate for dental applications.